SLCMV and CMD-field survey dataset using a standard BSP for Cambodia, Laos and Vietnam - Chittarath, Khonesavanh; Oeurn, Samoul; Lee, Hang; Trinh Xuan, Hoat; Jiménez Polo, Jenyfer; Cuéllar, Wilmer Jose (International Center for Tropical Agriculture, 2021)
Standard surveillance and diagnostic protocols need to be evaluated and implemented at regional level, for early warning and coordination of rapid responses among neighbor countries. This dataset provides a description of 2020 surveillance data for cassava mosaic disease (CMD) in Laos, East Cambodia and Northern Vietnam, indicating location of the surveyed fields, and presence/absence of visual symptoms. The image data was accessed and validated through the PestDisPlace platform by experts working with CMD. All data was collected using standard protocols (e.g. 60 observations per Hectare). Detailed information is available upon request.